The Implementation of Quizizz Media to Improve Students’ English Learning Achievement at SMP Negeri 9 Ambon - Relmasira, Mega Victoria; Lekawael, Rosina; Pesiwarissa, Rice (LPPM Universitas Bina Bangsa, 2025)
This study aims to improve the English learning achievement of students at SMP Negeri 9 Ambon through the use of Quizizz media. The method employed was Classroom Action Research (CAR), which was conducted in two cycles involving 20 students from class VIII-10. Data were collected through observation, documentation, and tests, then analyzed using a descriptive comparative approach. The findings revealed that the students’ average score in the pre-cycle was 69 with a mastery percentage of 50%. After implementing Quizizz, students’ achievement improved in Cycle I with an average score of 78.75 and a mastery rate of 70%, and further increased in Cycle II with an average of 88.1 and 100% mastery. These results indicate that the application of Quizizz can enhance students’ engagement in learning and positively impact their English learning achievement